Educational cartoon as an edutainment strategy to combat pediatric obesity: an innovative proposal from the PODiaCar Project - Gianvincenzo Zuccotti; Valeria Calcaterra; PODiaCar Team (Italian Journal of Pediatrics)
Abstract Pediatric obesity is an escalating global health concern with profound physical and psychological impacts, both in the short and long term. The EU-funded initiative, "Fight against Pediatric Obesity: from a Predictive Tool for Type 2 Diabetes and Cardiovascular Disease Risk to Healthy Educational Programs" (PODiaCar), seeks to address childhood obesity through a comprehensive, multidimensional strategy. A key component is a cartoon titled Grandma Wilma’s Tales, created to promote healthy lifestyles among young children and their families. Targeted at preschoolers and early primary school students, the cartoon uses an “edutainment” strategy, blending education with entertainment, to keep children engaged while they learn. The story follows a young boy named Vitto and his dog Buzz as they discover the dangers of poor diet and inactivity and the benefits of a healthy, balanced lifestyle. By using simple language, engaging visuals, and relatable characters, the cartoon informs and motivates children to make healthier choices in everyday life. Its design focuses on accessibility and appeal, helping children absorb important health messages in an enjoyable way. This initiative highlights the power of visual communication and storytelling in health education. Teaching children about balanced diets and active living from an early age can build a strong foundation for lifelong wellness. Supporting and sharing projects like PODiaCar at national and international levels is essential for developing future public health strategies and encouraging innovative, child-focused educational approaches.